PENGARUH PANDANGAN IKLAN, DIGITAL MARKETING, DAN CITRA MEREK TERHADAP KEPUASAN PENUMPANG PADA PT BIRO PERJALANAN WISATA NUSA INDAH - Ng, Kelvin; Nainggolan, Nora Pitri Nainggolan (LPPM Universitas Putera Batam, 2023)
This study aims to examine the effect of advertising views, digital marketing, and brand image on passenger satisfaction at PT Nusa Indah Travel Bureau. This research uses a type of quantitative approach. The population of this study are all users or people who have used products and services from PT. Nusa Indah Travel Bureau with unknown population size. The research sample used the Cochran formula with a total of 100 respondents using the non-probability sampling method. The collected data will be analyzed using descriptive statistical tests, data quality tests, classical assumption tests, influence tests and hypothesis testing. The results of the multiple linear regression analysis show that advertising views have an effect of 20.5% on passenger satisfaction. Digital marketing has an influence of 33.5% on passenger satisfaction. Brand image has an influence of 31.7% on passenger satisfaction. Analysis of the coefficient of determination (R2) shows that the views of advertising, digital marketing and brand image have a strong influence on passenger satisfaction at PT. Nusa Indah Travel Bureau with a proportion of influence of 67.7% The results of the hypothesis test show that both partially and simultaneously views of advertising, digital marketing, and brand image have a positive and significant effect on passenger satisfaction at PT Nusa Indah Travel Bureau.